2011
DOI: 10.1016/j.biomaterials.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The ROS scavenging and renal protective effects of pH-responsive nitroxide radical-containing nanoparticles

Abstract: The ultimate objective of nanoparticle-based therapy is to functionalize nanomedicines in a micro-disease environment without any side effects. Here, we reveal that our pH-responsive nitroxide radical-containing nanoparticles (RNP(pH)) disintegrate within the renal acidic lesion and act as scavengers of reactive oxygen species (ROS), leading to a relief of acute kidney injury (AKI). RNP(pH) was prepared using amphiphilic block copolymers possessing 2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO) moieties via amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 25 publications
2
122
0
1
Order By: Relevance
“…The amount of laccase and TEMPO in the final product can be roughly estimated around 10 mg/g (GM) and 15 mg/g (GM) , respectively. TEMPO is considered as non-toxic and it is used in a wide number of biomedical applications (Narain, 2011;Yoshitomi, Hirayama, & Nagasaki, 2011;Yoshitomi, Yamaguchi, Kikuchi, & Nagasaki, 2012). Therefore, neither residual components of the oxidation reaction should be considered as drawbacks in future practical applications of this new biomaterial.…”
Section: Characterization Of Eolfgmentioning
confidence: 99%
“…The amount of laccase and TEMPO in the final product can be roughly estimated around 10 mg/g (GM) and 15 mg/g (GM) , respectively. TEMPO is considered as non-toxic and it is used in a wide number of biomedical applications (Narain, 2011;Yoshitomi, Hirayama, & Nagasaki, 2011;Yoshitomi, Yamaguchi, Kikuchi, & Nagasaki, 2012). Therefore, neither residual components of the oxidation reaction should be considered as drawbacks in future practical applications of this new biomaterial.…”
Section: Characterization Of Eolfgmentioning
confidence: 99%
“…In previous studies, we had developed polymeric micelles composed of an amphiphilic block copolymer possessing TEMPO moieties as side chains and confirmed their ROS-scavenging activity in vivo or in vitro [31][32][33][34].…”
Section: Suppression Of Blood Activation By Nrp Beadsmentioning
confidence: 76%
“…Core-shell-type polymeric micelles containing nitroxide radicals have already been developed for the treatment of oxidative stress injuries and in vivo ESR imaging [29,30]. It has been confirmed that they not only strongly scavenge ROS in vivo or in vitro but also significantly prevent oxidative stress damage in an cerebral ischemia-reperfusion injury model in rats [31], renal ischemia-reperfusion injury model in mice [32] and a neuron cell line used as a model for Alzheimer's disease [33,34], in which excess ROS is generated. In the process, we have hypothesized that ROS-scavenging characteristics play a crucial role in blood activation and coagulation when blood comes in contact with material surfaces.…”
Section: Introductionmentioning
confidence: 98%
“…We developed a nitroxide radical-containing nanoparticle (RNP) for use as a nanomedicine for oxidative stress injury [16][17][18][19][20] and as a bioimaging nanoprobe for MRI and ESRI [21], which is composed of a poly(ethylene glycol)-b-poly(methylstyrene) block copolymer possessing TEMPO moieties via an amine linkage (PEG-b-PMNT) [22]. This PEG-b-PMNT forms core-shell-type micelles in the physiological environment; the cumulant average diameter of the RNP is about 40 nm, and it emits an intense ESR signal.…”
Section: Introductionmentioning
confidence: 99%
“…The RNP was confirmed to have long-term spin circulation in the blood due to the formation of polymeric micelles in the blood stream. Disintegration of RNP is caused by protonation of the amino groups in response to acidic pH, which typically occurs at inflammation sites, since amino groups are introduced into the hydrophobic segments of amphiphilic block copolymers [17]. Along with the decreasing in pH, ESR signals of RNP gradually change from broad to sharp triplets.…”
Section: Introductionmentioning
confidence: 99%